As faces da esfinge: contos de Clarice Lispector em sua tradução para o inglês - Araújo, Vladimir Lima (2022)
For several decades now the work of Clarice Lispector has been presented somehow or other to audiences in other countries. Among the translations made into English of the Claricean universe two of them have stood out: the first, by Giovanni Pontiero for the book of short stories A Legião Estrangeira, published under the title Foreign Legion (1986); and the second, more recent, by Katrina Dodson for all of Clarice's short stories, published in English under the title The Complete Stories (2015). Clarice Lispector's writing, far from being conventional, brings in its essence aspects that require the translator of her texts to dive deeply into a work whose language essentially acts as the protagonist. Therefore, in the two translations mentioned above, there are outstanding differences regarding the approach to the complexity of Clarice's writing. For the analyses presented here, the short stories “Temptation” and “A sincere friendship” were selected. For this thesis we have adopted as main theoretical basis the assumptions brought to Translation Studies by Venuti (1995) and Berman (2007, 2009): text fragmentation and repetition, linguistic and cultural distances, foreignization and domestication. Following along these paths and having Clarice's work as object, we will seek an immersion in search of the paths taken by the two translators in the often obscure pathways of the author of The Hour of the Star.